Macromedia® FreeHand®MX : Training from the Source - Schulze, Patti (Adobe Press, 2003)
Macromedia FreeHand MX: Training from the Source is a thorough ground-up text that is part of the popular series from Macromedia Press. Macromedia FreeHand MX leads you step-by-step through the program's most important new features as you work through several, practical graphic design projects that reflect real-world problems, solutions, and practices. With Macromedia FreeHand MX: Training from the Source you'll learn how to use the program's robust tools to create a logo and then create a corporate identity package all in one document, organize and manage complex illustrations, and even create an animation that will then be used in a Flash animation. The book's project-based tutorial approach allows you to work through the lessons in the book at your own pace, using the practice files on the companion CD-ROM to get started immediately with the program!